Advances in the application of chitosan as a sustainable bioactive material in food preservation. Issue 14 (6th August 2022) - Yu, Dawei; Yu, Zijuan; Zhao, Wenyu; Regenstein, Joe M.; Xia, Wenshui
Abstract: Chitosan is obtained from chitin and considered to be one of the most abundant natural polysaccharides. Due to its functional activity, chitosan has received intense and growing interest in terms of applications for food preservation over the last half-century. Compared with earlier studies, recent research has increasingly focused on the exploration of preservation mechanism as well as the targeted inhibition with higher efficiency, which is fueled by availability of more active composite ingredients and integration of more technologies, and gradually perceived as "chitosan-based biofilm preservation." In this Review, we comprehensively summarize the potential antimicrobial mechanisms or hypotheses of chitosan and its widely compounded ingredients, as well as their impacts on endogenous enzymes, oxidation and/or gas barriers. The strategies used for enhancing active function of the film-forming system and subsequent film fabrication processes including direct coating, bioactive packaging film and layer-by-layer assembly are introduced. Finally, future development of chitosan-based bioactive film is also proposed to broaden its application boundaries. Generally, our goal is that this Review is easily accessible and instructive for whose new to the field, as well as hope to advance to the filed forward.